PERANCANGAN LABORATORIUM PADA CAMPURAN ASPHALT CONCRETE-BINDER COURSE (AC-BC) DENGAN MENGGUNAKAN ASPAL PEN 60/70 DAN ZEOLIT ALAM SEBAGAI FILLER - , ALFIAN SALEH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia has a wealth of natural resources is high, including mineral resources into pavement materials. Utilization of natural resources such as raw materials pavement still has not been developed, especially to overcome the problems related to premature pavement damage. Asphalt Pen. 60/70 and natural zeolite is a natural asset that can be used, but the study linked the two materials are still not widely practiced. Merging the two materials in the testing done with the design of the test specimen using 5 filler content variation, the variation of1 (100% stone dust: 0% natural zeolite), variation 2 (75% stone dust: 25% natural zeolite), variation 3 (50% stone dust: 50% natural zeolite), variations4 (25% stone dust: 75% natural zeolite) and variation 5 (0% stone dust: 100% naturalzeolite). Having obtained the optimum bitumen content of each variation then testing Marshall with soaking time of 0,5 hours and 24 hours, then the Indirect Tensile Strength testing. The results were obtained for the optimum bitumen content variation 1 is 5,8%